A Comparative study of Daiva's Sin and its Evolution in the Stories of Ancient Iran and Ta'ziehs of Daiva's Tying Thumb Based on Six Poetic Verses - Mahdi mohamadi; Adel Meghdadian; Abolfazl Tajik (مجله مطالعات ایرانی)
1.Introduction The presence of demons as evil and demonic beings in epic literature as well as religious epic narrations is very abundant. Hence, the demons' story is also considered a style in religious erature. In ancient religious texts, the demon was the main manifestation of evil and the devil's army. For example, in Zoroastrian texts, vicious traits such as greed, anger and aggression were appeared in the form of demons such as Az, Ishma and Aži dahāka. By sinning human beings, these demons gained power and were weakened by their piety. In different historical periods, the use of this word has not been limited to the attributes of vice, but sometimes it was also used to refer to the enemy or all non-Zoroastrians. (See Akbari Mafakher, 2008, p. 53-55). In the Islamic era, the word demon maintained its negative position. As time has passed since the arrival of Islam in Iran, this ancient concept has become more and more intertwined with Islamic texts, so that it finds a place in religious texts, such as taziyehs. In taziyeh, the demon no longer refers to the evil of antiquity and Zoroastrian texts. It is a creature that has chosen the wrong path and not inherently evil. In taziyeh ceremonies, ting the demon's thumb also appears in this form. (See Karami and Parsapour, 2016, p. 73). The demon of taziyeh lived thousands of years before the creation of Adam, and he is depicted as a male, huge and violent creature that has been harassing creatures. Because of this behavior, Imam Ali (PBUH) appeared to him in the form of a teenager slapped him hard and tied his thumb with a rope or a strand of hair. The demon wanders until the creation of Adam. After that, he goes to the service of the divine prophets, but none of them can heal the wound caused by the slap or open his thumb. Eventually, with the advent of Islam, the demon went to the Prophet and at his command, Imam Ali opened his thumb and the demon became a Muslim. This research seeks to answer the following questions about this story. In the pre-human era, what sin did the demon commit that was punishable? What are the similarities between the sins of demons, as expressed in the Taziyeh texts, and the actions of ancient demons? How did his punishment relate to the nature of his sin? During his imprisonment, what process of transformation did the demon undergo that led to his conversion to Islam? In this research, it is assumed that the greatest sin of the demon is oppression and extravagance against the natural world and then his arrogance towards God, which is manifested in the form of aggression. The slap seems to have been the punishment for the sin of arrogance, and tying the thumb, the punishment for the sin of oppression and extravagance, because in this way, the demon could no longer eat. For a long time, demon's life was marked by pain and hunger, His repeated frustrations caused him to despair of his situation and wish for death. His greed and arrogance disappeared in this austerity and rationality replaced it.   2.Methodology The method of this research is descriptive-comparative. In this study, by comparing the texts of the taziyeh of the demon's tying thumbs, a description of the demon's sin and his transformation process is obtained. Then, examines the extent of its compatibility with pre-Islamic texts and its derivations from Islamic sacred texts, by matching it with the ancient heritage.   3.Discussion One of the styles of religious literature is the demons' stories (cf. Karami and Parsapour, 2016, p. 73). The demons, along with the gods and human beings form a triad of mythological thought systems. Of course, demons were not bad from the beginning (Cf. Amuzgar, 1992, p. 16-22). And, they may have found their way among the gods, but some of their betrayals and turning their backs on the gods and associating with human beings made them removed them from the ranks of the gods. The demon also had a sinful background. Anger, covetousness, greed and such traits, practically led the demons into rebellion against the gods. In Islamic literature, there is also talk of demons. This autonomous being is known in Quranic-hadith texts by the keyword of jinn. The general meaning of the demon as a metaphor of the devil, Iblis, Satan, the Giant, the Jinn, the Al , davālpā , Nasnas and other evil creatures can be traced in the oral and official texts of the Islamic period (Ebrahimi, 2013, p. 71). in the literature of religious myths, such as the fiction literature of taziyeh, these jinns are also referred to as demons. The tribe of jinns or demons are themselves divided into two categories. The jinn of the believer and the jinn or the demons of the infidel. The unbelief of demons in taziyeh texts is very similar to those told in the mythological literature of ancient Iran. The aim of this research is to study the nature of sin of demons and their transformation in the myths of ancient Iran and compare it with the taziyeh of tying the thumb of a demon. Mythical demons also have a lot in common with the attributes of vice and the army of ignorance in Islamic traditions. For example, the demon Az, who has an insatiable characteristic and is devoured by the devil at the end of the world, is one of the demons of Shahnameh. In Persian and Zoroastrian mythology, the demon Az, is one of the strongest allies and accomplices of the devil. In fact, he is in charge of the army. The description of Az in Bundahis (Primal Creation) is as follows: "Az is the demon who … will not accumulate and doesn't satisfied if everyone gives him the desire of the universe. (Bahar, 2018, p. 120). From a comparative point of view, , it is not without merit to mention that according to one of the texts of Ta'ziyeh, Imam Ali considers tying the hand of a demon in order to prepare creation for the creation of human. In this way, the conditions of human creation in Avestan texts are compatible with this text of taziyeh, because because in the thought of ancient Iran, after Devil was raised by Jahi, he killed cows and kiyomars in the universe (material world). After that, the battle between Ahuraians (good people) and the devil began in order to prepare the ground for the creation of human. (See Hinnells, 1989, pp. 89-91). Trumad/ Tromti or the demon of arrogance is a female demon who creates arrogance and selfishness, Just the opposite of Sepandarmaz who is a symbol of humility (ibid., p. 45). "Ishma" (the demon of anger (Avestan) aēšma is the enemy of "Soroush") which means the demon of anger and extreme violence and is the embodiment of cruelty. (Hinnells, 1989, p. 83; Bahar, 2018, p. 120). There have been other demons in the mythological literature of Iran. The demon of death (Oshidari, 1992, p. 106), the demon of lust and anxiety who are the children of the devil. (Zomorodi and Nazari, 2011, p. 62; Hinnells, 1989, p. 88). Aži dahāka is a destructive demon and devours a third of the creatures and damages fire, water and plants at the end of the world (Hinnells, 1989, p. 85). Although demons are inherently evil in the mythological literature of ancient Iran, in addition to their own control over their sin, they have also gained power through the sin of human beings. But between the demons of post-Islam and the demons of Iran, the difference is that the demon no longer refers to evil in ancient times and Zoroastrian texts, but is a creature who has chosen the wrong path and not inherently evil. Demon is the name of a group of Aryan gods that were worshiped by the people of Iran (Akbari Mafakher, 2008, p. 52) But gradually they faced the gods of Asura or Ahura and became equivalent to the devil (see Amuzgar, 1992, p. 16-18). One of the characteristics of demon stories in Islamic taziyeh texts is the stages of demon evolution. This evolution is explained in the texts of Taziyeh as follows: He was slapped hard by Imam Ali (PBUH) and his two thumbs are tied by the Imam with a palm leaf or in other words with a hair strand. The slap was so severe that his face was wounded and until he is healed by the Imam, blood and pus will come from it. (G2) Humiliation of the demon is one of the goals of Imam Ali which is stated in this text: I am a lion and you are a lowly fox foe me / O shameless, You are being captured by me now (p. 179). Therefore, in explaining of this research, it should be said that what is mentioned in the stories of the demons as a punishment for the sins of the demon, that is, the tying of his thumb by Imam, is so that the demon can no longer express himself through his own oppression, and this is what caused the demon to repent and eventually be forgiven. This study examines the issue of similarity of Iranian mythical demons, and it determines the degree of similarity and distinction between mythical demons and demons of religious literature, by examining the types of demons in mythological literature and its similarity with the vicious traits in Islam and how the demon repents after being punished for its work.   4.Conclusion The symbol of the "demon" as a symbol of evil in ancient times continued to live in the Islamic era with changes. This change in the texts of Taziyeh which is related to tying the thumb of the demon is mostly seen in the fact that although the demon is a bad being, he is not an inherent evil and is acquired, and he can be guided and developed by being in the right way. The demon has vices in the pre-creation period, so that his greatest sin is his cruelty and extravagance towards nature. The demon stories in ancient Iran and the taziyeh of "The tying of the demon's thumb by Imam Ali (PBUH)" similarly have considered the reason for the limitation of demons to provide the conditions for human creation. Infinite killing, high aggression and demon's arrogance against God were his most important sins that took away the ability to understand from the demon. Thus the demon had become a disorder for creation. Hence, the demon in the story of tying the thumb is very similar to the ancient demons such as Az, Ishma and Aži dahāka and a number of other demons such as arrogance and idolatry. His way of getting rid of moral vices is similar to the way of getting rid of the demon Az, that is, suffering from hunger, which causes contentment, curbs greed, anger, and oppression, and then, it brings wisdom and reasoning in the evolved existence of the demon.